Digital Storytelling in Experiential Tourism Destination Imaging - Didit Darmawan; Rischa Afifatin Nasqa (SYNERGY: Jurnal Bisnis dan Manajemen, 2026)
This literature study examines digital storytelling in experience-based tourism destination branding, focusing on narrative construction and its mechanisms in shaping tourist perceptions and decisions. The analysis reveals that effective storytelling construction requires authentic thematic foundations, emotional plot development, and integrated use of human characters, meaningful visuals, and audio elements. Consistency across platforms, audience interactivity, and multi-stakeholder collaboration strengthen the narrative ecosystem. Success is measured by the virtuous cycle between story, visitation, and post-visit narratives shared by tourists. Key elements influencing tourist perceptions include authenticity, emotional resonance, imaginative capacity, narrative structure, source credibility, functional visuality, and temporal urgency. Psychological mechanisms involve identification, narrative transportation, cognitive script formation, social validation, value resonance, expectation shaping, and post-visit memory construction. The study contributes theoretically by extending understanding of digital storytelling mechanisms in destination branding. Practically, it provides a framework for destination managers to design authentic, consistent narratives that build long-term emotional connections with tourists seeking meaningful travel experiences